O-96 Phase 2 randomised controlled trial of future care planning in patients with advanced heart disease. (1st September 2015) - Denvir, Martin A; Highet, G; Boyd, K; Robertson, S; Cudmore, S; Donald, L; Haga, K; Weir, C; Murray, Scott A
Abstract : Background: Patients with advanced heart disease typically have poor prognosis despite optimal therapy and rarely receive coordinated future care planning (FCP). Aim: To explore whether a FCP intervention is acceptable, feasible and deliverable to patients (and families) with advanced heart disease following a recent unscheduled hospital admission. Methods: Patients with acute coronary syndrome (ACS) or acute heart failure (HF) were screened using a prognostic scoring tool. Patients with a 12 month estimated mortality risk of 20% or greater were randomly allocated to either early (upon discharge) or delayed (after 12 weeks) FCP for 12 weeks. The intervention combines holistic needs-assessment by a cardiologist with creation of a written/shared FCP and nurse-led care in the community. Primary outcome is quality of life of patients and carers assessed using questionnaires. Results: 50 patients (and 32 carers) – 22% with ACS, 68% HF and 10% valvular heart disease. There were 5 deaths and 5 withdrawals. For the whole cohort mean age is 81.1 years (SD = 8.6), 60% male, mean Charlson comorbidity index was 4.2 (SD = 1.7), median Canadian frailty scale = 5 (Mildly frail). Intervention and follow up is currently on-going. Discussion: Findings demonstrate that the intervention and outcome measures were feasible and deliverable. Further analysis be presented at the meeting. Conclusion: Future Care planning represents a key generic mechanism by which patients with advanced heart disease can begin planning for a good death. Randomised trial evidence is one approach by which this could be adopted into routine clinical practice in a socialised healthcare system.